2021
DOI: 10.1086/714359
|View full text |Cite
|
Sign up to set email alerts
|

What to Expect When It Gets Hotter

Abstract: We use temperature variation within narrowly defined geographic and demographic cells to show that exposure to extreme temperature increases the risk of maternal hospitalization during pregnancy. This effect is driven by emergency hospitalizations for various pregnancy complications, suggesting that it represents a deterioration in underlying maternal health rather than a change in women's ability to access health care. The effect is larger for black women than for women of other races, suggesting that without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…32 The consequences also extend to the larger health systems by increasing the burden on already stretched health resources due to increased rates of caesarean sections, 33 hospitalisation, 34 emergency department visits, 35 36 and outpatient and inpatient health facility visits. [37][38][39] Research gaps Research on heat and health has been mostly restricted to stand-alone individual studies with relatively small sample sizes, poor-quality data from household surveys or healthcare facilities, considerable variation in research methodology, and limited geographical and temporal coverage. 13 19 Most studies have insufficient power to answer questions about which specific aspects of heat exposures (eg, timing and duration), which temperature patterns/thresholds (eg, night-time or day-time, or averages) are most harmful for different clinical conditions, and in which climate zones, settings, and subgroups.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…32 The consequences also extend to the larger health systems by increasing the burden on already stretched health resources due to increased rates of caesarean sections, 33 hospitalisation, 34 emergency department visits, 35 36 and outpatient and inpatient health facility visits. [37][38][39] Research gaps Research on heat and health has been mostly restricted to stand-alone individual studies with relatively small sample sizes, poor-quality data from household surveys or healthcare facilities, considerable variation in research methodology, and limited geographical and temporal coverage. 13 19 Most studies have insufficient power to answer questions about which specific aspects of heat exposures (eg, timing and duration), which temperature patterns/thresholds (eg, night-time or day-time, or averages) are most harmful for different clinical conditions, and in which climate zones, settings, and subgroups.…”
Section: Open Accessmentioning
confidence: 99%
“…Several studies have shown that exposure to heat in utero negatively affects health throughout the life course, such as increased risks of stunting 32. The consequences also extend to the larger health systems by increasing the burden on already stretched health resources due to increased rates of caesarean sections,33 hospitalisation,34 emergency department visits,35 36 and outpatient and inpatient health facility visits 37–39…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In complement to scholarship on acute disaster events, scholars have also studied the effects of enduring changes in weather. The most consistent evidence on harmful health effects emerges from exposure to extreme heat during pregnancy [86,87], which operates through multiple mechanisms, including maternal heat stress, and in lower-income contexts, nutritional deprivation and infectious disease exposure [88].…”
Section: Extreme Temperaturesmentioning
confidence: 99%